The Effectiveness of a Psychological Counseling Program on Developing Future Optimism among Students of the Department of Physical Education and Sports Sciences at Zakho University - Omar, Jehan Hussein; Abdullah, Musab Mohammed; Mohammed, Safad Mudhafar (Universitas Muhammadiyah Metro, 2024)
The current study aimed to identify the level of future optimism among students of the College of Education, specializing in Physical Education and Sports Sciences, and to determine the significance of differences based on specific demographic variables (gender, residence, marital status). Additionally, the study aimed to construct a psychological counseling program for the sample individuals. The research sample consisted of 39 male and female students selected purposively. The study employed descriptive and experimental methodologies, and SPSS (Statistical Package for the Social Sciences) was used to analyze the data. The results indicated a low level of future optimism, with no significant differences observed in the sample attributed to demographic variables or the effectiveness of the psychological counseling program. Based on the findings, recommendations, and suggestions were presented after the study. The study highlights the importance of fostering future optimism among university students, particularly in physically demanding disciplines, to promote their overall well-being and resilience.